Sistem Penunjang Keputusan Pemilihan Pakan Kering Anak Kucing Menggunakan Simple Additive Weighting - Sedyarsa, Hanif Fauzan; Akbar, Mutaqin (Universitas Muhammadiyah Sorong, 2025)
This study aims to develop a decision support system for selecting dry cat food for kittens using the Simple Additive Weighting (SAW) method. The system is designed to assist cat owners in choosing available food products at Galaxy Petshop based on several important criteria, namely price, protein content, carbohydrates, quality of raw materials, age suitability, and moisture content. The decision-making process involves normalizing the data, assigning weights to each criterion, and calculating preference values to rank the alternative cat foods. The system is implemented using the Python programming language and tested with six product alternatives. The results indicate that the system is capable of providing the best alternative recommendation based on the criteria, with Proplan Kitten as the top alternative with a preference value of 0.755, followed by Excel Kitten (0.660) and Royal Canin Kitten (0.630). This system has proven effective in helping users determine the most suitable cat food according to nutritional needs and budget, and it has potential for further development by adding more criteria and integrating with digital platforms.